Luther's Challenge: The Power of Greed in Our Common Home. Issue 1 (March 2016) - Torvend, Samuel
Abstract: When faced with growing poverty, corrupt business practices, and the power of banking houses and lobbyists, Luther drew on his theological anthropology in order to discern the devastating power of greed in human relationships. And yet, as he admitted, greed was and is a clever master of human ambition, accepted by leaders in church, commerce, and government. His teaching on the power of greed was in continuity with the Christian tradition and yet broke new ground in his recognition that this vice possesses a social, institutional nature.